Business Model Canvas sebagai Media Pembelajaran Praktikum Bisnis bagi Mahasiswa: Studi Literatur - Difi Dahliana; Muhammad Yulian Ma'mun; Nazmi Soraya; Lisda Aisyah (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2025)
Business learning in higher education still faces the problem of the gap between theory and practice. Conventional methods that are too concept-oriented make it difficult for students to understand the relationship between business components in real terms. This condition demands a more contextual, interactive, and easy-to-understand practicum approach. The Business Model Canvas (BMC) is a comprehensive yet straightforward alternative learning instrument that presents a complete picture of the business model through nine main blocks. This article presents a literature study by examining the scientific publications of the last five years (2020–2025) regarding the application of BMC in business learning. The results of the study show that BMC is efficacious in improving students' conceptual understanding, analytical skills, creativity, and entrepreneurial motivation. Furthermore, BMC encourages project-based learning through group work, simulations, and the preparation of business models that resemble real practices. However, the implementation of BMC still faces challenges in the form of time constraints, technical difficulties, and a culture of passive learning. Thus, BMC integration is important as an innovative learning strategy that can strengthen students' readiness to face the dynamics of the business world.